THE MAGNETIC PROPERTIES MEASUREMENT OF COIL FOR GRAVITATIONAL ACCELERATION DETERMINATION - Salawane, Cherly; Supriyadi, Supriyadi; Talapessy, Ronaldo; Risakotta, Mirtha Yunitha Sari (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
The value of the gravitational acceleration of the earth above the earth’s surface depends on the position of the latitude and longitude of the earth’s surface, in other words, because the shape of the earth’s surface is not round like a ball. The magnitude of gravity is not the same everywhere on the surface of the earth. The purpose of this study is to analyze the value of the earth’s gravitational acceleration in a laboratory using a current balance with a graphical method. Fluctuations in the value of the magnetic field strength (B) and the value of the electric current strength (i) on the current balance cause the value of laboratory gravitational acceleration (glab) to vary in the transfer of electric charge (q) according to coil type. The magnitude of the earth’s gravitational acceleration value obtained in a laboratory with a current balance for each type of coil is as follows: SF-37 glab-nr=9.89 m/s2, SF-38 glab-nr=9.90 m/s2, SF-39 glab-nr=9.76 m/s2, SF-40 glab-nr=9.95 m/s2, SF-41 glab-nr=9.75 m/s2 dan SF-42 glab-nr=9.93 m/s2. The results obtained indicate that the value of the earth’s gravitational acceleration in a laboratory close to the literature value is the value of the glab-nr in the SF-37 coil type of 9.89 m/s2.